2012
DOI: 10.1007/s12576-011-0190-7
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal testosterone supplementation alters puberty onset, aggressive behavior, and partner preference in adult male rats

Abstract: The objective of this study was to investigate whether prenatal exposure to testosterone (T) could change the body weight (BW), anogenital distance (AGD), anogenital distance index (AGDI), puberty onset, social behavior, fertility, sexual behavior, sexual preference, and T level of male rats in adulthood. To test this hypothesis, pregnant rats received either 1 mg/animal of T propionate diluted in 0.1 ml peanut oil or 0.1 ml peanut oil, as control, on the 17th, 18th and 19th gestational days. No alterations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…In this study, except for reduction of sperm motility, the other effects (reduction of Sertoli cells, Spermatocyte and Spermatid, sperm count and testosterone concentration), were not observed in male rats exposed to exogenous testosterone at day 20 of their fetal life; this could be explained by the difference in time exposure to androgen as in experimental group І it was administered during the male programming window [14], and time of first peak of sexual differentiation of hypothalamus [10], therefore resulted in more severe effects on reproductive function. The rats of experimental group П were exposed to exogenous testosterone on the last day of the gestational period, therefore the hypothalamus-pituitary-gonad axis had been programmed before.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In this study, except for reduction of sperm motility, the other effects (reduction of Sertoli cells, Spermatocyte and Spermatid, sperm count and testosterone concentration), were not observed in male rats exposed to exogenous testosterone at day 20 of their fetal life; this could be explained by the difference in time exposure to androgen as in experimental group І it was administered during the male programming window [14], and time of first peak of sexual differentiation of hypothalamus [10], therefore resulted in more severe effects on reproductive function. The rats of experimental group П were exposed to exogenous testosterone on the last day of the gestational period, therefore the hypothalamus-pituitary-gonad axis had been programmed before.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore it has been shown that prenatal exposure of male rat to Di-n-Butyl Phthalate (DBP) (anti-androgen, which reduces androgen level) decreases the activity level of testicular steroidogenic enzymes, as well as testosterone level in adults [16]. Another study demonstrated that prenatal exposure of male rat to testosterone propionate, during days 17-19 of gestation, will lead to reduction of plasma testosterone level during adulthood [10]. Rams exposed to testosterone during their development, showed a higher level of plasma testosterone at 20 weeks of age, while a lower level had been seen at the age of 30 weeks [24].…”
Section: Discussionmentioning
confidence: 99%
“…Organization of the neuronal circuits by testosterone and/or its metabolites predetermines the behavioral responses to the activational effects of sex hormones later in life. Besides the sensitive period of early—prenatal and perinatal development ( 15 , 27 ), increasing amount of evidence supports the hypothesis that pubertal hormones (re)organize the brain and determine a variety of adult behaviors during adolescence ( 36 , 37 ) or outside of the classic critical periods of neurodevelopment ( 38 ). An overview of the results of some experiments investigating sex differences and the role of testosterone in anxiety-like behavior, with particular regard to the age of animals with hormone manipulation and analysis of the outcomes, is provided in Table 1 .…”
Section: The Role Of Testosterone In Anxiety-like Behavior Of Rodentsmentioning
confidence: 96%
“…On the other hand, when the sleep duration was further decreased to mimic the chronic sleep debt present in humans, no significant change in sexual motivation or behavior was observed [54]. Supplementation of testosterone has been observed to be an efficient means of maintaining and improving sexual response in adults and aged male rats [55,56]. There is evidence that the supplementation of testosterone (T) combined with estradiol (E2) shows better results [57].…”
Section: Effects Of Sleep Deprivation On Male Sexual Behaviormentioning
confidence: 99%